Difficulties of teaching English at primary school - Jurayeva Zarnigor Bo’stonovna; D.V.Subanova (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2023)
This article discusses the difficulties faced by teachers when teaching English to primary school students. It highlights the types of difficulties and their solution. In this article some recommendations and suggestions are given by several methodologists